The Influence of Operating Cash, Liquidity, Leverage and Profitability on Financial Distress on Mining Sector Companies Listed on Idx Period 2015-2019 - Afiezan, Adam; Gunarsih, Jessica; Salim, Ardiyan; Etania, Cassandra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to examine and analyze the effect ofOperating Cash Flow, Liquidity, Leverage and Profitability have an effect on Financial Distress in mining sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The research method used in this study uses quantitative research methods with quantitative descriptive research that is explanatory research. The population of this research is allMining sub-sector companyThere are 43 companies listed on the Indonesia Stock Exchange. The sample of this research is 7 companies with purposive sampling technique. The data analysis method used is multiple linear regressions. The results of the f test where f count 416,363 > f table 2.68 with a significant level < 0.05 indicatesOperating Cash Flow, Liquidity, Leverage and Profitability simultaneously has an effect on Financial Distress in mining sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The results of the t-test research where Liquidity and Leverage variables do not have a significant effect on Financial Distress in mining sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period and only Operating Cash Flow and Profitability have an effect on Financial Distress in mining sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The results of the analysis of the coefficient of determination obtained the Adjusted R2 value of 0.980, meaning that the variation of the variable Operating Cash Flow, Liquidity, Leverage and Profitability in explaining the Financial Distress variable is 98%, while the remaining 2% is explained by othersÂ